Water And Salt Water Absorption, Hygrothermal And Tribological Propertires Of Nickel Zinc Ferrite Magnetorheological Elastomers - Chang, Fan Ru (Universiti Sains Malaysia, 2018)
Magnetorheological Elastomers (MREs) known as new material underdevelopment research to offer high damping capability for many applications use to replace limitations usage of rubber as a damper. Many research studies only focused on its material properties such as magnetorheological effect and lack of studies on mechanical properties of its specific applications. Mechanical properties such as hardness, tribology characteristic and salt water and water absorption with hygrothermal effect will be further studies on wear performance of Magnetorheological Elastomers on marine equipment applications. Isotropic, anisotropic and anisotropic with added N330 carbon black filler of Ni Zn Ferrite Magnetorheological Elastomers (MREs) are prepared with Ni Zn Ferrite filler, Ni1 - xZnxFe2O4 particles weight fraction of 70%. Images of Scanning Microscopy Electron (SEM) and Energy Dispersive X-Ray Analysis (EDX) are identified with the presence of the structure of Ni Zn Ferrite in the natural rubber matrix. In salt water and water absorption and hygrothermal effect, an effect on the percentage of increase in weight of samples during immersion within the period of 336 hours will be analyzed. Tribology characteristics of these three compounds are studied by pin-on-disc machine based on the perspective of the average specific coefficient of friction (COF), specific wear rate, and loss of wear volume initial condition and after water and salt water immersion with different speeds and loads applied. Wear performance of three compounds of MREs is directly proportional to its hardness. Anisotropic Ni Zn Ferrite MREs with added carbon black filler given highest hardness value of 90.78; least effect on salt water and water absorption and hygrothermal effect; better wear performance with a low average specific coefficient of friction, specific wear rate and least loss of wear volume. Therefore, it is most suitable use for future application in a wet environment for a long period.